Analytical Formulation for Temperature Evolution in Flat Wheel-Rail Sliding Surfaces. (12th November 2018) - Alizadeh Otorabad, Hossein; Hosseini Tehrani, Parisa; Younesian, Davood; Sietsma, Jilt; Petrov, Roumen
Abstract : Studying the temperature evolution of the thermally affected zone (TAZ) of sliding surfaces is crucial because of its influence on microstructural evolution, wear, and fatigue. Due to the complexity of thermal analysis of sliding bodies, relationships that predict their surface temperature evolution are very helpful because they can be used as time-dependent boundary conditions; this makes the thermal analysis of sliding bodies independent. In this paper, by assuming thermal contact conductance (TCC) at the sliding common surface, the differential equation governing the thermal analysis of the wheel-rail sliding is solved throughout a wheel flat. The temperature evolution of wheel and rail surfaces and the heat partitioning factor are among the main results. Finally, the equations obtained for wheel and rail surface temperatures are applied to a freight wagon and a passenger car as two real cases. The results are discussed and compared to existing data in the literature and a solid agreement is achieved.